Automated Vehicle Failure: The First Pedestrian Fatality and Public Perception. Issue 8 (August 2022) - Tapiro, Hagai; Wyman, Amy; Borowsky, Avinoam; Petzoldt, Tibor; Wang, Xuesong; Hurwitz, David S.
On the evening of March 18, 2018, an automated vehicle (AV) struck and killed a 49-year-old pedestrian in Tempe, AZ, as she crossed the road. From about 2 weeks before the crash through April 30, 2018, an online survey, designed to address U.S. public perceptions of AVs among vulnerable road users, was distributed to adult U.S. residents. Survey responses were collected from 1, 409 individuals. This survey provided a unique opportunity to examine the "first failure effect" of an AV on U.S. public perceptions of AV technology. The survey considered response date, age, gender, education, place of residence, and primary transportation mode as explanatory variables, and general impression, trust, acceptance, and perceived safety as independent variables. After the crash, general impression, trust, acceptance, and perceived safety levels dropped significantly. Perceived safety did not return to its precrash level through to the end of the survey, whereas all other measures returned to their precrash levels approximately 1 month postcrash. On average, younger, educated, and male respondents held a more positive attitude of AVs than older, less educated, and female respondents. Findings indicate that high-visibility negative events may affect how individuals perceive and interact with AVs.